Is it necessary to use forced air warming in core endourological procedures where warmed intravenous and irrigation fluids are routinely used?. (September 2019) - Azhar, Fowz; Dyer, James E; Clarke, Laurence
Objective: Perioperative hypothermia is an important consideration for all surgical specialties, but susceptibility may vary between them. Current guidance on prevention of this does not differentiate between specialties. We hypothesise that in core endourological surgery, the use of warmed irrigation sufficiently protects patients from hypothermia and that forced air warming (FAW) does not provide any added benefit. Materials and methods: Between November 2015 and January 2016, all case notes were reviewed for patients who had undergone core urological procedures. Data collated included age, body mass index, procedure length, perioperative temperatures and warming methods used. The sample population was stratified according to warming devices used. The difference in temperature change between groups was assessed using analysis of variance (ANOVA) and in specific groups using the Student's t -test. Perioperative hypothermia was defined as a finishing temperature < 36.0°C or a temperature drop of greater that 1.0°C. Results: Perioperative hypothermia occurred in 2 out of 226 patients, both from those receiving FAW, warmed irrigation and warmed intravenous (IV) fluid. No significant difference was noted between all groups in terms of absolute temperature change (ANOVA P = 0.111). Furthermore, there was no significant change in absolute temperature when comparing groups with FAW, warmed irrigation and warmed IV fluid with those with warmed irrigation and warmed IV fluid alone. Conclusion: The routine use of FAW in core endourological surgery may not be necessary. In most procedures, particularly those of short duration, there appears to be no added benefit in using FAW in combination with warmed irrigation and IV fluid. Level of evidence: 3b